2022
DOI: 10.1002/esp.5306
|View full text |Cite
|
Sign up to set email alerts
|

The Negro River in the Anavilhanas Archipelago: Streamflow and geomorphology of a complex anabranching system in the Amazon

Abstract: The evolution of the fluvial landscape is the result of controls and processes that can be observed by the adjustments a river makes to its hydrological regime. The Negro River is the sixth-largest river in the world by water volume and contains two complex anabranching systems, the Anavilhanas and Mariuá archipelagos, and despite its importance, there is a lack of hydrological survey data on its multichannel reaches.The objective of this study was to analyse the fluvial dynamics of the lower Negro River and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The attenuation and storage effects of floodplains are well known in hydrogeomorphological and applied studies on floodplain management and restoration [33,34]. Yet, our finding regarding the role of the complex morphology of the fluvial corridor as a foundational element in understanding flood properties and hydrological connectivity patterns is in accordance with results from other studies on large rivers [35][36][37][38][39]. In the context of the Solimões-Amazon River, Meade et al [40] observed that apart from the shifted timing of tributary inputs, the subdued extremes of discharge, differing only by a factor of 2 or 3 throughout the year, reflects the seasonal storage of substantial water volumes within the intervening floodplain during rising stages.…”
Section: Discussionsupporting
confidence: 90%
“…The attenuation and storage effects of floodplains are well known in hydrogeomorphological and applied studies on floodplain management and restoration [33,34]. Yet, our finding regarding the role of the complex morphology of the fluvial corridor as a foundational element in understanding flood properties and hydrological connectivity patterns is in accordance with results from other studies on large rivers [35][36][37][38][39]. In the context of the Solimões-Amazon River, Meade et al [40] observed that apart from the shifted timing of tributary inputs, the subdued extremes of discharge, differing only by a factor of 2 or 3 throughout the year, reflects the seasonal storage of substantial water volumes within the intervening floodplain during rising stages.…”
Section: Discussionsupporting
confidence: 90%
“…The Anavilhanas National Park has approximately 350,000 hectares of area and about 400 islands, making it the second largest river archipelago in the world [ 10 , 13 , 14 ]. Its aquatic environment is formed by black waters of the Negro River, which are poor in nutrients and have high concentrations of organic compounds, resulting an acidic pH 4.6–4.8 while the dissolved oxygen level was 5.0–5.5 mg/L [ 15 , 16 ]. It is important to note that compared to the Flutuante dos Botos, the city harbor of Novo Airão exhibited a higher degree and nature of pollution, influenced by boats pollutants influx and city sewage.”…”
Section: Methodsmentioning
confidence: 99%
“…The study involved the participation of three adult dolphins named Curumim, Chico, and Priscila. These dolphins ( Inia geoffrensis ) were visually identified with the assistance of the employees at Flutuante dos Botos, who possess expertise in recognizing individual dolphins based on their scars, pigmentation patterns, and behaviors [ 15 , 16 ]. It should be noted that since these are free-ranging animals, estimating factors such as approximate age and sex becomes inherently challenging.…”
Section: Methodsmentioning
confidence: 99%
“…Recent advances have been made through the use of mapping from remotely sensed imagery (e.g. Marinho et al, 2022) and from detailed investigations of bar sedimentology (Nicholas et al, 2013; Słowik, 2016). However, the development of anastomosing patterns often occurs over substantial time periods.…”
Section: Introductionmentioning
confidence: 99%